The Employee Performance and The Influence of Leadership Style and Work Environment - Muhammad Ridwan; HD. Melva Sitanggang; Amril Anas (Jurnal Manajemen Bisnis, 2023)
The purpose of this research is to ascertain the impact of Leadership Style and Work Environment on Employee Performance at the PT Jaya Sari Arta Sei Rotan Branch. This study use quantitative tools and an associative approach to causal linkage. In this study, the population consists of all 25 employees of PT Jaya Sari Arta Sei Rotan Branch. And 25 participants were chosen as a sample to be used as respondents in this study. The sample strategy employs saturation sampling techniques in conjunction with a nonprobability sampling approach. Data is gathered via distributing and distributing questionnaires, which will be completed by 25 respondents. Using the SPSS 17 programme, the data analysis technique employs the validity test, reliability test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression test, hypothesis testing (t test, f test, and coefficient of determination test (R2). The findings revealed that Leadership Style has a partially positive and significant effect on Employee Performance. Employee Performance is influenced in part by the work environment. Employee performance at PT Jaya Sari Arta Sei Rotan Branch is influenced by both leadership style and work environment.